Analysis of Monopoly Practices and Business Competition in the Limboto Traditional Market - Mardiana, Andi; Jerita, Nurlian; Pakaya, Delviranti; Rahim, Ziamudin G; Abay, Rizky Firmansyah (Scimadly Publishing, 2024)
This study analyzes monopoly practices and business competition in the traditional market of Limboto, Gorontalo. The Limboto traditional market is an important trading center in the region involving various types of goods and services. This study aims to explore how monopolistic practices and competitive dynamics affect market conditions, prices of goods, and the welfare of traders and consumers. In addition, business competition in the traditional Limboto market shows unique characteristics, including informal collaboration between traders and the role and influence of the local market on competition. This research is expected to provide insight for policymakers and stakeholders in formulating strategies to improve market efficiency and local economic welfare.